Photoproduction of pseudoscalar mesons on 1 p -shell nuclei at high energies and forward angles; Physical Review C; Vol. 108 - Iss. 4 - Fiks (Fix) A. I. Alexander Ivanovich (2023, 2023)
I address the issue of coherent and incoherent photoproduction of pseudoscalar mesons on nuclei at high photon energies in the peripheral region, characterized by small momentum transfer. The reactions considered give prominent background to photoproduction in the electromagnetic field of a nucleus. For this reason, a detailed knowledge of their cross sections is necessary for correct determination of the radiative decay widths of neutral mesons. Particular attention is paid to transitions to the discrete bound levels, as well as to the giant resonance states. Numerical results are presented for photoproduction of η mesons on 12C.